An apamin-sensitive Ca(2+)-activated K(+) current in hippocampal pyramidal neurons - Stocker, Martin (The National Academy of Sciences, 1999)
In hippocampal and other cortical neurons, action potentials are followed by afterhyperpolarizations (AHPs) generated by the activation of small-conductance Ca(2+)-activated K(+) channels (SK channels). By shaping the neuronal firing pattern, these AHPs contribute to the regulation of excitability and to the encoding function of neurons. Here we report that CA1 pyramidal neurons express an AHP current that is suppressed by apamin and is involved in the control of repetitive firing. This current presents distinct kinetic and pharmacological features, and it is modulated differently than the apamin-insensitive slow AHP current. Furthermore, our in situ hybridizations show that the apamin-sensitive SK subunits are expressed in CA1 pyramidal neurons, providing a potential molecular correlate to the apamin-sensitive AHP current. Altogether, these results clarify the discrepancy between the reported high density of apamin-binding sites in the CA1 region and the apparent lack of an apamin-sensitive current in CA1 pyramidal neurons, and they may explain the effects of this toxin on hippocampal synaptic plasticity and learning.